Manfaat EVA Sebagai Predikator EPS (Studi Empiris Bank Umum Milik Pemerintah Periode 2011 - 2015) - Wibowo, Yohan Henri (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The aims of this study is to find the empirical evidence, that the Economic Value Added positive (EVA> 0) can predict the Earnings per Share (EPS). In this study, the collecting of data method is the documentative the Annual Financial Statements have been audited (FS Audited) of all government-owned commercial bank).The approach in this study is Descriptive Quantitative and associative.The sample in this study is the 4 (four) commercial bank, which BBRI, BBNI, Mandiri, and BBTN.The results of research that found empirical evidence that EVA> 0 can predict the EPS, This is revealed in simple linear regression equation Y = 76.315 + 3,052X + Îµ, R Square = 0.981, Sig. 0,000. Keywords: EVA, EPS